Factors associated with gastrointestinal disorders in the first year of late and moderate premature infants - Leonardo Bigolin Jantsch; Vanessa da Silva Barzotto; Ethel Bastos da Silva (Universidade Federal do Ceará, 2020)
Objective: to analyze the factors associated with the development of gastrointestinal disorders in the first year of life of late and moderate premature infants. Methods: longitudinal study, which followed infants born late and moderate, during the first year of life, via telephone, to develop gastrointestinal disorders, in the maternal perception. Data collected using the Likert scale, in the assessment of acute condition, and analyzed under comparison of frequency and odds ratios (p<5% and 95% Confidence Interval) between variables. Results: the most frequent gastrointestinal injuries in the assessment of the first months of life were colic and vomiting, which reduced the intensity, the closer to the infant's first year of life, followed by the diarrheal condition that maintained constant intensity throughout the first year. Conclusion: the study has implications for the identification of risk factors, in view of the vulnerability of the premature population, still little described in the literature.